Psychometric properties of the 10-item Connor-Davidson Resilience Scale in Chinese military personnel - Tu, Zhihao; He, Jingwen; Wang, Ziying; Song, Mingfang; Tian, Jianquan; Wang, Chuan; Ba, Jianbo; Shen, Xinghua (Frontiers in Psychology, 2023)
Abstract Background: The 10-item Connor-Davidson Resilience Scale (CD-RISC-10) is a widely used assessment of resilience. However, psychometric properties of the Chinese version of CD-RISC-10 have not been well investigated in Chinese military personnel sample. Methods: 3,129 Chinese military personnel completed the CD-RISC-10, Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS). Among them, 528 recruits completed the CD-RISC-10, SAS, and SDS again after 3-month basic military training (BMT). Meanwhile, the commanding officers were asked to rate recruits’ training performance on Training performance rating scale for recruits (TPRS). Confirmatory factor analysis (CFA) was implemented to examine the single-factor model of the CD-RISC-10, and multigroup CFA was conducted to test measurement invariance across military rank (officers vs. enlisted), gender (male vs. female), and time (before and after 3-month BMT). Internal consistency was evaluated using Cronbach’s α and McDonald’s ω, and test-retest reliability was tested using intra-class correlation coefficient (ICC). The criterion-related validity of CD-RISC was evaluated by Pearson’s correlation analysis between the CD-RISC-10 total score and SAS scores, SDS scores, and training performance ratings. Results: The single-factor model of the CD-RISC-10 showed adequate fit (CFI = 0.955 to 0.970, TLI = 0.943 to 0.962, RMSEA = 0.059 to 0.072) in all examined subsamples (male, female, officer, and enlisted), and strict invariance was also supported across military rank, gender, and time (ΔCFI ≤ 0.001, ΔTLI ≤ 0.005, ΔRMSEA ≤ 0.006). The CD-RISC-10 showed good internal consistency in all subsamples (Cronbach’s α > 0.93 and McDonald’s ω > 0.93) and good test-retest reliability (ICC = 0.88). Moreover, concurrent and predictive validity with the SAS and SDS scores were good (r = -0.68 to -0.49, p < 0.001). The resilience level of recruits at the beginning of BMT was significantly associated with training performance rated by supervisors after traning (r = 0.29, p < 0.001).